APPROACH TO THE CHILD WITH RECURRENT INFECTIONS - AlKhater, Suzan A. (Medknow Publications & Media Pvt Ltd, 2009)
Children with a history of recurrent, severe, or unusual infections present a diagnostic challenge. It is important to maintain a high index of suspicion for the diagnosis of immunodeficiency, for early diagnosis and treatment can improve outcome. Differentiation between infections caused by common risk factors, or immune dysfunction should be based on a detailed history and physical examination and, if indicated, followed by appropriate laboratory studies. This paper aims at providing guidelines for the evaluation of children with recurrent infections. It provides an overview of the diagnostic approach including important details required from the history, physical examination, and an appropriate choice of screening test to be ordered.